2011
DOI: 10.1007/s10443-011-9205-z
|View full text |Cite
|
Sign up to set email alerts
|

Rubber Impact on 3D Textile Composites

Abstract: is an open access repository that collects the work of Arts et Métiers ParisTech researchers and makes it freely available over the web where possible. Abstract A low velocity impact study of aircraft tire rubber on 3D textile-reinforced composite plates was performed experimentally and numerically. In contrast to regular unidirectional composite laminates, no delaminations occur in such a 3D textile composite. Yarn decohesions, matrix cracks and yarn ruptures have been identified as the major damage mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…The observed damage mechanisms in 3D woven composites are very different from those encountered in classical laminates due to the specific architecture of such materials. Due to the complexity of the encountered damage mechanisms, only very few impact modelling studies [18] can be found in the literature and are dedicated to very specific architectures.…”
Section: Introductionmentioning
confidence: 99%
“…The observed damage mechanisms in 3D woven composites are very different from those encountered in classical laminates due to the specific architecture of such materials. Due to the complexity of the encountered damage mechanisms, only very few impact modelling studies [18] can be found in the literature and are dedicated to very specific architectures.…”
Section: Introductionmentioning
confidence: 99%
“…These features lead to the application of complex shaped braided composite structures in impact protection areas, such as debris impact protection of supersonic aircraft and spaceship. Heimbs et al [28] developed the meso and macro-scale to study elastic energy stored during impact. Elias et al [29] presented the ODM-PMC model to investigate damage mechanisms of 3D woven composites and estimated the residual properties of the material.…”
Section: Low Velocitymentioning
confidence: 99%
“…Thus, the higher the ratio of 3D warp yarns to straight warp yarns is, the higher the impact resistance is. However, a reinforcement with a high amount of undulated yarns has reduced in-plane properties [14]. Therefore, the reinforcement with 55% 3D warp yarns seems to offer a good compromise between impact damage tolerance and good stiffness properties.…”
Section: Introductionmentioning
confidence: 99%
“…This work follows on an investigation performed within a national research project on vulnerability of composite structures, which partly addressed the impact performance of different 3-D interlock carbon woven composites. The investigation which was both experimental and numerical [13][14][15] showed that the major damage mechanisms were yarn decohesion, matrix cracks and a few yarn ruptures mainly located at the back side of the composite plate. Three different reinforcement types with different ratios of 3D warp yarns to straight warp yarns (30%, 55% and 100%) were tested [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation